Are gifted adolescents more satisfied with their lives than their non-gifted peers? - Bergold, Sebastian; Wirthwein, Linda; Rost, Detlef H.; Steinmayr, Ricarda (Frontiers in Psychology, 2015)
Studies investigating the life satisfaction of intellectually gifted and nongifted students are scarce and often suffer from methodological shortcomings. We examined the life satisfaction of gifted and nongifted adolescents using a rather unselected sample of N = 655 German high-school students (n = 75 gifted), adequate comparison groups of nongifted students, and a clear definition of giftedness (general intelligence g > 2 SD above the mean). There was no difference in life satisfaction between gifted and nongifted adolescents (d < |0.1|). Girls reported somewhat lower life satisfaction scores than boys (d = 0.24). However, this result was not specific to giftedness but was instead found across the entire sample. Thus, gifted girls were not found to be especially unsatisfied with their lives. Our findings support previous research showing that giftedness is not a risk factor for impaired psycho-social well-being of boys or girls.